2013
DOI: 10.2174/157016313804998924
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future of Nutrigenomics and its Influence on Drug Development

Abstract: The importance of nutrition in disease prevention and treatment has gained much attention with the emergence of next generation sequence technologies allowing full-genome sequencing at reduced cost in weeks rather than months. The vast genetic information needs to be efficiently channeled into a useful format to provide applicability for improved health and treatment of disease. Recently, it also led to the birth of nutrigenomics, which facilitates the investigation of the effects of nutrition on gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Some encouraging and promising studies have shown results in the context of cancer [23, 24]. The potential of nutrigeno/proteomics is considerable [25] and includes impacts on design and development of new drugs [26, 27] but a broad consensus still lacks about safety and risk assessment using such new approaches in postgenomics medicine [28, 29]. …”
Section: New Pathways To Personalized Nutritionmentioning
confidence: 99%
“…Some encouraging and promising studies have shown results in the context of cancer [23, 24]. The potential of nutrigeno/proteomics is considerable [25] and includes impacts on design and development of new drugs [26, 27] but a broad consensus still lacks about safety and risk assessment using such new approaches in postgenomics medicine [28, 29]. …”
Section: New Pathways To Personalized Nutritionmentioning
confidence: 99%